2008
DOI: 10.1111/j.1540-5885.2009.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Innovation Projects: Capabilities and Governance Mechanisms*

Abstract: This paper is concerned with how firms in a project-based industry cooperate in technological innovation projects in the construction industry. The main focus of the paper is on the sharing of capabilities in cooperative innovation projects and how these cooperations are governed. A knowledge-based perspective is applied, and four cooperative innovation projects in the construction industry are compared. Based on the case studies, a set of propositions is defined. First, a cooperation aimed at a mutual strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 57 publications
(89 reference statements)
1
84
0
3
Order By: Relevance
“…Earlier investigations have shown that a collaborative climate based on trust and commitment facilitates: economic performance in terms of decreased cost overruns (Iyer and Jha, 2005), time performance (Chan et al, 2003;Phua and Rowlinson, 2004), quality and customer satisfaction (Phua and Rowlinson, 2004), environmental performance (Cole, 2000;Shen and Tam, 2002), work environment (Rwamamara, 2007; Table 2 Proposed relationships among procurement procedures and project performance. (2008) Yang (2007), Woksepp and Olofsson (2008) Cole (2000), Shen and Tam (2002) Cole ( Nilsson, 2008), and innovation (Ling, 2003;Harty, 2008;Manley, 2008;Bosch-Sijtsema and Postma, 2009;Rutten et al, 2009). These findings suggest that collaborative climate may influence how procurement procedures affect project performance in a role as a mediator or as a moderator.…”
Section: Collaborative Climate As Mediating or Moderating Factormentioning
confidence: 72%
See 1 more Smart Citation
“…Earlier investigations have shown that a collaborative climate based on trust and commitment facilitates: economic performance in terms of decreased cost overruns (Iyer and Jha, 2005), time performance (Chan et al, 2003;Phua and Rowlinson, 2004), quality and customer satisfaction (Phua and Rowlinson, 2004), environmental performance (Cole, 2000;Shen and Tam, 2002), work environment (Rwamamara, 2007; Table 2 Proposed relationships among procurement procedures and project performance. (2008) Yang (2007), Woksepp and Olofsson (2008) Cole (2000), Shen and Tam (2002) Cole ( Nilsson, 2008), and innovation (Ling, 2003;Harty, 2008;Manley, 2008;Bosch-Sijtsema and Postma, 2009;Rutten et al, 2009). These findings suggest that collaborative climate may influence how procurement procedures affect project performance in a role as a mediator or as a moderator.…”
Section: Collaborative Climate As Mediating or Moderating Factormentioning
confidence: 72%
“…Careful partner selection (through bid evaluation based on suitable soft parameters) considering desired competences, experiences and attitudes can therefore reduce cost growth (Chua et al, 1997;Iyer and Jha, 2005;Wardani et al, 2006) and time overruns (Chan and Kumaraswamy, 1997;Assaf and Al-Hejji, 2006). Furthermore, it can improve quality (Yasamis et al, 2002), environmental performance (Shen and Tam, 2002), work environment (Ai Lin Teo et al, 2005;Ling et al, 2009;Rajendran and Gambatese, 2009), and innovation (Manley, 2008;Bosch-Sijtsema and Postma, 2009;Caldwell et al, 2009 A domestic contract means that subcontractor selection is made by the contractor, while the client (or the construction manager) selects the subcontractors in nominated contracts (Shoesmith, 1996). The selection can also be made jointly by both parties in collaboration (Eriksson and Nilsson, 2008).…”
Section: Relationships Between Bid Evaluation Choices and Project Permentioning
confidence: 98%
“…Consequently, we view two distinct relational governance mechanisms in this research: mutual influence and cultural similarity of cooperating parties. These mechanisms have been shown as relevant antecedents of innovativeness and cooperation performance in recent empirical studies of vertical buyer-supplier cooperations (Bosch-Sijtsema and Postma, 2009;Linnarsson and Werr, 2004;Muthusamy and White, 2006).…”
Section: Effects Of Operational Governancementioning
confidence: 93%
“…The current research on governance in Western NPD collaborations demonstrates the importance of contractual governance (Mayer and Argyres, 2004;Ryall and Sampson, 2009) and relational governance (Bosch-Sijtsema and Postma, 2009;Lawson et al, 2009) for enhancing the outcomes of NPD collaborations, including knowledge acquisition and collaboration satisfaction (e.g., Poppo and Zenger, 2002). Knowledge acquisition is defined as the degree of information acquired via collaboration that extends a firm's knowledge base about user needs, new product development, and production and manufacturing processes, and is a major objective in NPD collaborations (Rindfleisch and Moorman, 2001;Lawson et al, 2009).…”
Section: The Transactional View Of Npd Collaborationsmentioning
confidence: 99%